ASSOCIATION OF DUODENAL EOSINOPHILIC INFILTRATE WITH HELICOBACTER PYLORI INFECTION, BUT NOT WITH FUNCTIONAL DYSPEPSIA - LEITE,Carine (2020)
ABSTRACT BACKGROUND: The role of Helicobacter pylori infection on eosinophilic infiltration in duodenal mucosa is poorly studied. An increase in the number of eosinophils in duodenum has been associated with functional dyspepsia. OBJECTIVE: To evaluate the influence of H. pylori infection on duodenal eosinophil count and the role of eosinophilic infiltrate of duodenum in functional dyspepsia. METHODS: Positive and negative H. pylori individuals were included. Both functional dyspeptic patients according to Rome III criteria (cases) and individuals without gastrointestinal symptoms (controls) were enrolled. They were submitted to upper endoscopy and H. pylori infection was verified by gastric histopathology and urease test. Eosinophils in the duodenal mucosa were counted in five high-power fields, randomly selected on slides of endoscopic biopsies. RESULTS: Thirty-nine H. pylori positive (mean age 40.5 and 69.2% women) and 24 negative patients (mean age 37.3 and 75% women) were included. The influence of the infection was observed in the duodenal eosinophil count, which was higher in infected individuals: median 13.2 vs 8.1 in non-infected individuals (P=0.005). When we analyzed patients according to symptoms, cases - mean age 39.6; 71.4% women - and controls - mean age 38.7; 71.4% women - had similar duodenal eosinophil count: median 11.9 and 12.6 respectively (P=0.19). CONCLUSIONS: We did not demonstrate association of duodenal eosinophil count with functional dyspepsia but found association with H. pylori infection.